Modified ZSM-5 molecular sieve catalyst as well as preparation method and application thereof

By introducing metal oxides and ions into ZSM-5 molecular sieves for modification, the problems of catalyst microporous structure limitation and insufficient acidity were solved, achieving highly selective and stable aromatic hydrocarbon preparation, and improving the catalytic performance and the yield of target products.

CN120984319APending Publication Date: 2025-11-21ENERGY RES INST OF SHANDONG ACAD OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511413237.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing ZSM-5 molecular sieve catalysts suffer from problems such as low macromolecular mass transfer efficiency and insufficient acidity characteristics due to the microporous structure limiting their use in the catalytic pyrolysis of plastics. This results in unsatisfactory selectivity for monocyclic aromatic hydrocarbons and a tendency to generate polycyclic aromatic hydrocarbons with low economic value and environmental toxicity.

Method used

The catalytic performance of ZSM-5 molecular sieves is enhanced by introducing metal oxides or metal ions such as Zn, Fe, Ni, Co, Mo and Zr. This includes improving texture and porosity, adjusting acidity, promoting aromatization reactions, and inhibiting catalyst aggregation and sintering.

Benefits of technology

The catalyst's selectivity and stability were improved, enhancing the yield and selectivity of the target product, monocyclic aromatic hydrocarbons, while reducing the formation of the byproduct, polycyclic aromatic hydrocarbons, thus achieving a highly efficient and environmentally friendly aromatic hydrocarbon preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120984319A_ABST
    Figure CN120984319A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid waste utilization, and particularly relates to a modified ZSM-5 molecular sieve catalyst and a preparation method and application thereof. The catalyst comprises a ZSM-5 molecular sieve and an active component, wherein the active component is loaded on the internal pore channel and the surface of the ZSM-5 molecular sieve; the active component comprises one or more of Zn, Fe, Ni, Co, Mo and Zr. By adjusting the loading capacity of the active components and the acidity of the catalyst and adjusting the interaction among the components of the catalyst, the high-density polyethylene plastic is used as a raw material, and the catalyst is simple in structure, single in element, free of oxygen element and low in by-product content; the modified ZSM-5 molecular sieve catalyst is simple in preparation process and low in production cost, and the catalyst takes high-density polyethylene plastic as a raw material, so that the yield of MAHs prepared by directional pyrolysis of the high-density polyethylene plastic as the raw material and the stability of the catalyst are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid waste utilization technology, specifically relating to a modified ZSM-5 molecular sieve catalyst, its preparation method, and its application. Background Technology

[0002] Monocyclic aromatic hydrocarbons (MAHs), especially benzene, toluene, ethylbenzene, and xylene (BTEX), are crucial basic chemical raw materials, widely used in the production of nylon, lubricants, dyes, and many other chemical products. Currently, industrial MAH production heavily relies on petroleum resources, primarily derived from the catalytic reforming of naphtha and the thermal cracking of petroleum hydrocarbons. Due to fossil fuel shortages and frequent global energy and environmental crises, there is an urgent need to develop an efficient, environmentally friendly, and low-carbon route for aromatic hydrocarbon production.

[0003] The catalytic pyrolysis of plastics to produce aromatics is a technology that efficiently converts waste plastics into high-value monocyclic aromatic hydrocarbons such as benzene, toluene, and xylene. While ZSM-5 molecular sieves are commonly used catalysts in this technology, their application has significant limitations: (1) the narrow microporous structure of ZSM-5 molecular sieves severely restricts the mass transfer efficiency of macromolecular plastic pyrolysis intermediates, easily leading to carbon deposition; (2) the inherent acidity of ZSM-5 molecular sieves results in insufficient deoxygenation capacity for oxygen-containing compounds, affecting product quality. These factors collectively lead to unsatisfactory selectivity for the target product, monocyclic aromatic hydrocarbons (MAHs), and instead promote the formation of byproducts, polycyclic aromatic hydrocarbons (PAHs). PAHs not only have low economic value but also possess environmental toxicity, hindering the greening and commercial application of this technology. Summary of the Invention

[0004] The purpose of this invention is to provide a modified ZSM-5 molecular sieve catalyst, its preparation method, and its application, thereby overcoming the shortcomings of the prior art. By modifying the ZSM-5 catalyst, it is made capable of pyrolyzing polyolefin plastics to prepare monocyclic aromatic hydrocarbons (MAHs) while simultaneously exhibiting high selectivity and stability.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a modified ZSM-5 molecular sieve catalyst, comprising a ZSM-5 molecular sieve and an active component, wherein the active component is loaded in the internal channels and surface of the ZSM-5 molecular sieve; The active component includes one or more of Zn, Fe, Ni, Co, Mo, and Zr.

[0006] The active components include metal oxides and metal ions. The metal oxides are mainly distributed on the surface of the ZSM-5 molecular sieve, while the metal ions are distributed in the internal channels of the ZSM-5 molecular sieve.

[0007] Specifically, the active metal oxide is one or more of ZnO, Fe2O3, NiO, CoO, Mo2O3, and ZrO2; the metal ion is Zn 2+ Fe 3+ Ni 2+ Co 2+ Mo 3+ and Zr 4+ One or more of them.

[0008] More specifically, the metal oxide and its metal ion are ZnO (Zn 2+ ), Fe2O3 (Fe 3+ ), NiO (Ni 2+ ), CoO (Co 2+ ), Mo2O3 (Mo 3+ ) and ZrO2 (Zr 4+ At least two of the following. For example, active metal oxides and their metal ions are ZnO (Zn 2+ ) and Fe2O3 (Fe 3+ ), or, ZnO (Zn 2+ ), Fe2O3 (Fe 3+ ) and or, ZnO (Zn 2+ ), NiO (Ni 2+ ) and CoO (Co 2+ ), or Mo2O3(Mo 3+ ) and ZrO2 (Zr 4+ ).

[0009] By modifying ZSM-5 molecular sieves with different metal oxides and their metal ion active components, the effectiveness of modified ZSM-5 molecular sieves in catalytic cracking, cyclization, and aromatization is enhanced, improving catalyst selectivity and stability, inhibiting catalyst aggregation and sintering, and thus realizing the directional catalytic pyrolysis process for preparing MAHs using high-density polyethylene plastic as raw material. The modified ZSM-5 molecular sieve catalyst prepared in this invention has the selectivity and stability for light aromatics. The main effects are analyzed as follows: On the one hand, metal doping can significantly improve the texture, acidity, and porosity of ZSM-5 molecular sieves, which is beneficial for regulating molecular sieve activity, improving catalytic performance, and increasing the yield and selectivity of target products; on the other hand, the addition of different metals can not only improve the acidity of the catalyst, but also accelerate certain reaction pathways, including decarboxylation, decarbonylation, and aromatization, thereby promoting the formation of aromatics, while also recycling coke.

[0010] In some other embodiments, the loading of the metal active component is 1-10 wt%; The modified ZSM-5 molecular sieve catalyst has a particle size of 30-40 mesh.

[0011] Specifically, the loading of active metal oxides is 1, 3, 5, 7, or 10 wt%; the particle size of the modified ZSM-5 molecular sieve catalyst is 30 or 40 mesh.

[0012] In some other embodiments, the silica-alumina ratio of the ZSM-5 molecular sieve is one or more of 25, 50, 85, 120, 200, and 300; The ZSM-5 molecular sieve has a particle size of 10-200 mesh. Specifically, the particle size of the ZSM-5 molecular sieve is 10, 30, 40, 50, 80, 100, 150 or 200 mesh.

[0013] In a second aspect, the present invention provides a method for preparing the modified ZSM-5 molecular sieve catalyst described in the first aspect, comprising the following steps: Pretreated ZSM-5 molecular sieves were added to a metal salt solution containing active components, and ultrasonically impregnated in equal volumes. After standing, drying and calcination, the modified ZSM-5 molecular sieve catalyst was obtained.

[0014] This invention employs an impregnation method to prepare modified ZSM-5 molecular sieve catalysts with different metal oxides as the main active components. By adjusting the metal loading and the acidity of the catalyst, the interaction between the components of the catalyst is regulated, effectively improving the yield and stability of MAHs prepared by directional pyrolysis of high-density polyethylene plastic as raw material.

[0015] In some other embodiments, the pretreatment method for the ZSM-5 molecular sieve is as follows: The ZSM-5 molecular sieve is calcined, then ground and sieved to obtain the pretreated ZSM-5 molecular sieve. The calcination atmosphere is air, the calcination temperature is 500-600℃, and the calcination time is 5-8 hours.

[0016] Specifically, the calcination temperature is 500, 550 or 600℃, and the calcination time is 5, 6, 7 or 8 hours.

[0017] In some other embodiments, the metal salt solution of the active component is one or more of soluble zinc salts, iron salts, nickel salts, cobalt salts, molybdenum salts, zirconium salts, and cerium salts; Preferably, the metal salt solution of the active component is Zn(CH3COO)2·2H2O, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O solution, Co(NO3)2·6H2O solution, or (NH4)6Mo7O solution. 24 One or more of the following: ·4H2O solution and Zr(NO3)4·5H2O solution.

[0018] In some other embodiments, the ultrasound duration is 10-30 minutes, and the settling time is 10-15 hours; The drying temperature is 100-110℃, and the drying time is 10-15 hours; The calcination atmosphere is air, the calcination temperature is 500-600℃, and the calcination time is 5-8 hours.

[0019] Specifically, the ultrasound time is 10, 15, 20, 25 or 30 min, the standing time is 10, 12, 14 or 15 h; the drying temperature is 100, 105 or 110 °C, and the drying time is 10, 12, 14 or 15 h. The calcination temperature is 500, 550 or 600℃, and the calcination time is 5, 6, 7 or 8 hours.

[0020] Thirdly, the present invention provides the application of the modified ZSM-5 molecular sieve catalyst described in the first aspect in the catalytic pyrolysis of polyolefin plastics to produce aromatic oil.

[0021] Fourthly, the present invention provides a method for producing aromatic oil by pyrolysis of polyolefin plastics, wherein the polyolefin plastics are mixed with the modified ZSM-5 molecular sieve catalyst described in the first aspect, and added to a two-stage fixed-bed reactor for pyrolysis under an inert atmosphere.

[0022] In some other embodiments, the mass ratio of the modified ZSM-5 molecular sieve catalyst to the polyolefin plastic is (1-4):1; The pyrolysis temperature is 450-700℃, and the pyrolysis time is 30-60 min.

[0023] Specifically, the mass ratio of the modified ZSM-5 molecular sieve catalyst to the polyolefin plastic is 1:1, 2:1, 3:1 or 4:1; the pyrolysis temperature is 450℃, 500℃, 550℃, 600℃, 650℃ or 700℃, and the pyrolysis time is 30, 40, 50 or 60 min.

[0024] The beneficial effects of this invention are: (1) To improve the selectivity and stability of light aromatic hydrocarbons in ZSM-5 molecular sieve catalysts, different metal oxides and their metal ions (ZnO, Zn) were added. 2+ ), Fe2O3 (Fe 3+ ), NiO (Ni 2+ ), CoO (Co 2+ ), Mo2O3 (Mo 3+ ) and ZrO2 (Zr 4+The active components enhance the effectiveness of ZSM-5 molecular sieves in catalytic cracking, cyclization, and aromatization, improve catalyst selectivity and stability, and inhibit catalyst aggregation and sintering, thereby enabling the directional catalytic pyrolysis of high-density polyethylene plastic to prepare MAHs. The main functions are as follows: Firstly, metal doping can significantly improve the texture, acidity, and porosity of ZSM-5 molecular sieves, facilitating the regulation of molecular sieve activity, improving catalytic performance, and increasing the yield and selectivity of target products. Secondly, the addition of different metals not only increases the acidity of the catalyst but also accelerates certain reaction pathways, including decarboxylation, decarbonylation, and aromatization, thereby promoting aromatic hydrocarbon formation and simultaneously recycling coke.

[0025] (2) The present invention uses an impregnation method to impregnate ZSM-5 molecular sieves with different metals in equal volumes to obtain modified ZSM-5 molecular sieve catalysts with supported oxides as active components. By adjusting the metal loading and the acidity of the catalyst, the interaction between the components of the catalyst is adjusted, which effectively improves the yield of MAHs prepared by directional pyrolysis of high-density polyethylene plastic as raw material and the stability of the catalyst.

[0026] (3) In this invention, the selectivity of MAHs and BTEX obtained by unmodified ZSM-5 molecular sieve catalysis was 85.34% and 54.7%, respectively, indicating poor catalyst stability. However, the zinc-modified ZSM-5 molecular sieve catalyzed the pyrolysis of polyolefin plastics to produce aromatic oil. With a metal oxide and its ion loading of 5%, a pyrolysis temperature of 500 °C, a pyrolysis time of 40 min, and a catalyst-to-raw material ratio of 2 / 1, the selectivity of MAHs and BTEX obtained after the reaction was 85.65% and 62.06%, respectively, with no catalyst sintering.

[0027] (4) The present invention uses high-density polyethylene plastic as raw material, which has a simple structure, single element, no oxygen element, and few by-products; the preparation process of modified ZSM-5 molecular sieve catalyst is simple and the production cost is low, and the catalyst has good selectivity and stability for the process of directional pyrolysis of high-density polyethylene plastic to prepare MAHs. Attached Figure Description

[0028] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0029] Figure 1 This refers to the two-stage fixed-bed reactor in Embodiment 1 of the present invention; Figure 2The aromatic selectivity diagrams for Examples 1-4 of the present invention under different pyrolysis conditions are shown, where (a) is the supported active metal salt, (b) is the loading of zinc oxide and its zinc ions, (c) is the pyrolysis temperature, and (d) is the mixing ratio of polyolefin plastic and metal-modified ZSM-5 molecular sieve catalyst. Figure 3 This invention illustrates the effect of the Si / Al ratio on the distribution of aromatic hydrocarbons in HDPE pyrolysis in Comparative Example 1. Detailed Implementation

[0030] Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be construed as limiting the scope of the invention. Specific conditions not specified in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Components whose manufacturers are not specified are all commercially available conventional products.

[0031] The structural defects of ZSM-5 molecular sieve lead to unsatisfactory mass transfer efficiency and weak deoxygenation ability, resulting in low yields of MAHs in the obtained aromatics and high yields of polycyclic aromatic hydrocarbons (PAHs), such as anthracene and phenanthrene. However, PAHs are toxic, easily pollute the environment, and have low production and use value.

[0032] This invention introduces different metal oxides and their metal ions (ZnO, Zn...) 2+ ), Fe2O3 (Fe 3+ ), NiO (Ni 2 + ), CoO (Co 2+ ), Mo2O3 (Mo 3+ ) and ZrO2 (Zr 4+ The active components enhance the effectiveness of ZSM-5 molecular sieves in catalytic cracking, cyclization, and aromatization, improve the selectivity and stability of the catalyst, and inhibit catalyst aggregation and sintering. Modified ZSM-5 molecular sieve catalysts with different metal oxides as the main active components are prepared by impregnation method, thereby realizing the process of directional catalytic pyrolysis to prepare MAHs from high-density polyethylene plastic as raw material.

[0033] The solution of the present invention is described below through specific embodiments: Example 1 A modified ZSM-5 molecular sieve catalyst and its preparation method, comprising the following steps: The ZSM-5 molecular sieve was modified by introducing active metals such as iron, nickel, cobalt, molybdenum and zirconium to prepare Fe / ZSM-5, Ni / ZSM-5, Co / ZSM-5, Mo / ZSM-5, Zr / ZSM-5 and Ce / ZSM-5 catalysts.

[0034] Unlike Example 1, in step (2), Fe(NO3)3·9H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and (NH4)6Mo7O are used respectively. 24 Zn(CH3COO)2·2H2O was replaced by ·4H2O and Zr(NO3)4·5H2O to support ZSM-5 molecular sieve catalysts with 5% modified metals. Other preparation methods were the same as in Example 1.

[0035] Depending on the metal salt solution used for loading, different metal-supported ZSM-5 catalysts were prepared using the following specific methods: Fe / ZSM-5 catalyst: Fe(NO3)3·9H2O solution (solvent mass is the same as ZSM-5 mass) is stirred until there is no obvious solid residue, then ultrasonicated in an ultrasonic cleaner for 20 min. ZSM-5 is then added, stirred evenly, and ultrasonicated again for 20 min. It is then allowed to stand at room temperature and normal pressure for 12 h, and then dried in an oven at 105 ℃ for 12 h (after taking it out, it is crushed into powder). Finally, it is calcined in a muffle furnace at 550 ℃ for 5 h, cooled to room temperature, pressed into tablets, and sieved to obtain 30~40 mesh particles, which are the Fe / ZSM-5 catalyst.

[0036] Ni / ZSM-5 catalyst: Ni(NO3)2·6H2O solution (solvent mass is the same as ZSM-5 mass) is stirred until there is no obvious solid residue, then ultrasonicated in an ultrasonic cleaner for 20 min. ZSM-5 is then added, stirred evenly, and ultrasonicated again for 20 min. It is then allowed to stand at room temperature and normal pressure for 12 h, and then dried in an oven at 105 ℃ for 12 h (after taking it out, it is crushed into powder). Finally, it is calcined in a muffle furnace at 550 ℃ for 5 h, cooled to room temperature, pressed into tablets, and sieved to obtain 30~40 mesh particles, which are the Ni / ZSM-5 catalyst.

[0037] Co / ZSM-5 catalyst: Co(NO3)2·6H2O solution (solvent mass is the same as ZSM-5 mass) is stirred until there is no obvious solid residue, then ultrasonicated in an ultrasonic cleaner for 20 min. ZSM-5 is then added, stirred evenly, and ultrasonicated again for 20 min. It is then allowed to stand at room temperature and normal pressure for 12 h, and then dried in an oven at 105 ℃ for 12 h (after taking it out, it is crushed into powder). Finally, it is calcined in a muffle furnace at 550 ℃ for 5 h, cooled to room temperature, pressed into tablets, and sieved to obtain 30~40 mesh particles, which are the Ni / ZSM-5 catalyst.

[0038] Mo / ZSM-5 catalyst: (NH4)6Mo7O 24• Add 4H2O solution (solvent mass is the same as ZSM-5 mass), stir until no obvious solid residue is found, then place in an ultrasonic cleaner and sonicate for 20 min. Add ZSM-5, stir evenly, and sonicate again for 20 min. Let stand at room temperature and normal pressure for 12 h, then place in an oven at 105 ℃ to dry for 12 h (after taking it out, crush it into powder). Finally, place it in a muffle furnace at 550 ℃ for 5 h, cool to room temperature, press into tablets, and sieve to obtain 30~40 mesh particles, which are the Ni / ZSM-5 catalyst.

[0039] Zr / ZSM-5 catalyst: A Zr(NO3)4·5H2O solution (solvent mass same as ZSM-5 mass) was stirred until no obvious solid residue remained, then ultrasonicated for 20 min in an ultrasonic cleaner. ZSM-5 was then added, stirred until homogeneous, and ultrasonicated again for 20 min. The solution was allowed to stand at room temperature and atmospheric pressure for 12 h, then dried in an oven at 105 ℃ for 12 h (after removal, it was crushed into powder). Finally, it was calcined in a muffle furnace at 550 ℃ for 5 h, cooled to room temperature, and pressed into tablets. 30-40 mesh particles were obtained as the Ni / ZSM-5 catalyst.

[0040] A two-stage fixed-bed reactor was used to directionally pyrolyze polyolefin plastics to prepare light aromatics, and the selectivity of the products obtained by the pyrolysis of the catalyst, such as monocyclic aromatic hydrocarbons (MAHs), benzene series compounds (BTEX), and polycyclic aromatic hydrocarbons (PAHs), was evaluated.

[0041] Two-stage fixed-bed reactor, such as Figure 1 As shown, the device includes a gas path and feeding unit, a tubular electric heater, a product collection and separation unit, and a gas product processing and analysis unit. The workflow is as follows: Nitrogen, as the carrier gas, carries the volatiles of the plastic into the tubular electric heater, which then passes through a pyrolysis and catalytic bed. The generated vapor products are condensed, the liquid aromatics are collected, and the remaining gas is introduced into an analytical instrument for real-time detection. The vertically placed tubular electric heater is the core area for the pyrolysis and catalytic reactions, and from top to bottom includes a pyrolysis zone, a catalytic zone, and a drying / indicating zone. The pyrolysis zone contains polyolefin plastic for pyrolysis; the catalytic zone contains a catalyst to catalytically convert the pyrolysis products into the target aromatics; and the drying / indicating zone contains color-changing silica gel to indicate gas humidity or adsorb moisture.

[0042] The catalytic pyrolysis conditions used were as follows: high-density polyethylene plastic was used as raw material, the pyrolysis temperature was 450 ℃, the pyrolysis time was 40 min, the ratio of catalyst to raw material was 2 / 1, and the nitrogen flow rate was 60 mL / min.

[0043] The catalysts Fe / ZSM-5, Ni / ZSM-5, Co / ZSM-5, Mo / ZSM-5, and Zr / ZSM-5, all with a loading of 5%, were evaluated, and the results are as follows: Figure 2 As shown in Figure (a), the results revealed that the catalyst prepared by introducing zinc modification exhibited the best performance. Therefore, zinc was selected as the optimal modifying element.

[0044] Example 2 A zinc-modified ZSM-5 molecular sieve catalyst and its preparation method, comprising the following steps: Unlike Example 1, in step (2), zinc ion solutions with concentrations of 0-10% were prepared. The other preparation steps were the same as in Example 1.

[0045] Using the same catalytic pyrolysis conditions as in Example 1, the catalytic performance of ZSM-5 molecular sieve catalysts modified with different zinc ion loadings was evaluated. The results are as follows: Figure 2 As shown in (b) of the diagram. Figure 2 (b) It was found that when the zinc loading was 0 wt.%, the MAHs and BTEX obtained by pyrolysis were 71.13% and 44.55%, respectively. The Zn / ZSM-5 with a loading of 5% showed the best catalytic effect, with selectivities of 85.65% and 62.06% for MAHs and BTEX, respectively.

[0046] Therefore, a loading of 5% was selected as the optimal loading for the modified ZSM-5 molecular sieve.

[0047] Example 3 The catalyst prepared by zinc modification with a loading of 5% and a silicon-to-aluminum ratio of 85, obtained in Example 2, was used to optimize the parameters of catalytic pyrolysis. Specifically, the pyrolysis time was kept constant at 40 min, the catalyst-to-feed ratio was 2 / 1, and the nitrogen flow rate was kept constant at 60 ml / min. The pyrolysis temperature was optimized by setting it to 450℃, 500℃, 550℃, 600℃, 650℃, and 700℃, respectively. The results are as follows. Figure 2 As shown in (c), the study found that the selectivity of MAHs and BTEX obtained after the reaction at a pyrolysis temperature of 450 °C was 85.65% and 62.06%, respectively, with no catalyst sintering phenomenon.

[0048] Example 4 The catalyst prepared by zinc modification with a loading of 5% and a silicon-to-aluminum ratio of 85, obtained in Example 2, was used to optimize the parameters of catalytic pyrolysis. Specifically, the pyrolysis temperature was kept constant at 450 °C, the pyrolysis time at 40 min, and the nitrogen flow rate at 60 ml / min. The catalyst-to-feed ratio was optimized by setting it to 2 / 1, 1 / 1, and 4 / 1, respectively. The results are as follows. Figure 2As shown in (d).

[0049] Studies have found that when the catalyst-to-feed ratio is 2:1, the selectivity of MAHs and BTEX after the reaction is 85.65% and 62.06%, respectively, with no catalyst sintering. When the catalyst-to-feed ratio is 1:1, the number and selectivity of effective active sites are poor, making it difficult to fully complete HDPE cracking and aromatization, leading to intermediate accumulation and easy coking, thus inhibiting the selectivity of the target aromatic hydrocarbon products. However, when the catalyst dosage is increased to 2:1, the increase in the total number of active sites effectively compensates for the adverse effects of Zn loading, allowing the advantages of Zn dehydrogenation and aromatization to be fully utilized. When the catalyst dosage is increased to 4:1, the increase in the number of active sites and selectivity is not significant. Therefore, a catalyst-to-feed ratio of 2:1 is the optimal ratio.

[0050] Comparative Example 1 A ZSM-5 molecular sieve catalyst and its preparation method, comprising the following steps: Carrier pretreatment: 15g of ZSM-5 molecular sieve powder with different silicon-to-aluminum ratios (0, 25, 50, 85, 120, 200, 300) was placed in a muffle furnace and calcined at 550 ℃ for 6h. Then, it was ground and sieved to prepare 200-mesh ZSM-5 molecular sieve carrier particles.

[0051] 15g of pretreated 200-mesh ZSM-5 molecular sieves with different silica-to-alumina ratios (0, 25, 50, 85, 120, 200, 300) were mixed with deionized water, stirred evenly, and then sonicated again for 20min. The mixtures were then allowed to stand at room temperature and atmospheric pressure for 12h, then dried in an oven at 105℃ for 12h (after removal, they were crushed into powder). Finally, they were calcined in a muffle furnace at 550℃ for 5h, cooled to room temperature, and then pressed into tablets and sieved to obtain 30-40 mesh particles, thus obtaining ZSM-5 molecular sieve catalysts with different silica-to-alumina ratios.

[0052] The pyrolysis conditions for the catalyst were as follows: using high-density polyethylene plastic as raw material, the pyrolysis temperature was 450 ℃, the pyrolysis time was 40 min, the ratio of catalyst dosage to raw material dosage was 1 / 1, and the nitrogen flow rate was 60 ml / min.

[0053] The performance of ZSM-5 molecular sieve catalysts with different silica-to-alumina ratios was verified, and the results are as follows: Figure 3 As shown, by Figure 3 It is known that the catalyst with a silica-to-alumina ratio of 85 exhibits selectivity of 85.34% for MAHs and 54.7% for BTEX. Therefore, ZSM-5 molecular sieve with a silica-to-alumina ratio of 85 was selected as the support. Figure 2In (d), when the zinc-supported ZSM-5 molecular sieve was used as a catalyst with a catalyst / feed mass ratio of 1 / 1, its selectivity for MAHs and BTEX was lower than that of the zinc-supported catalyst with a silica-alumina ratio of 85. This may be because the introduction of Zn altered the acidic structure of the catalyst, with some Brønsted acid sites being substituted or covered. Simultaneously, the aggregation of Zn species and pore blockage may further reduce the number of effective active sites and the selectivity. Under these conditions, the catalyst struggled to fully complete the HDPE cracking and aromatization conversion, leading to intermediate accumulation and easy coking, thus inhibiting the selectivity of the target aromatic hydrocarbon products.

[0054] In summary, through extensive experimental screening, this invention has determined the optimal ZSM-5 silicon-aluminum ratio of 85, the optimal loaded metal being zinc, the optimal metal loading being 5%, the optimal pyrolysis temperature being 450℃, and the optimal catalyst-to-raw material ratio being 2 / 1 for the directional pyrolysis process of preparing MAHs from waste high-density polyethylene plastics. These results in higher reaction efficiency and higher selectivity for MAHs.

[0055] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A modified ZSM-5 molecular sieve catalyst, characterized in that, It includes ZSM-5 molecular sieve and active components, wherein the active components are loaded in the internal pores and surface of ZSM-5 molecular sieve; The active component includes one or more of Zn, Fe, Ni, Co, Mo, and Zr.

2. The modified ZSM-5 molecular sieve catalyst according to claim 1, characterized in that, The loading of the active component is 1-10 wt%; The modified ZSM-5 molecular sieve catalyst has a particle size of 30-40 mesh.

3. The modified ZSM-5 molecular sieve catalyst according to claim 1, characterized in that, The ZSM-5 molecular sieve has a silica-to-alumina ratio of one or more of 25, 50, 85, 120, 200, and 300. The ZSM-5 molecular sieve has a particle size of 10-200 mesh.

4. A method for preparing the modified ZSM-5 molecular sieve catalyst according to any one of claims 1-3, characterized in that, Includes the following steps: Pretreated ZSM-5 molecular sieves were added to a metal salt solution containing active components, and ultrasonically impregnated in equal volumes. After standing, drying and calcination, the modified ZSM-5 molecular sieve catalyst was obtained.

5. The method for preparing the modified ZSM-5 molecular sieve catalyst according to claim 4, characterized in that, The pretreatment method for the ZSM-5 molecular sieve is as follows: The ZSM-5 molecular sieve is calcined, then ground and sieved to obtain the pretreated ZSM-5 molecular sieve. The calcination atmosphere is air, the calcination temperature is 500-600℃, and the calcination time is 5-8 hours.

6. The method for preparing the modified ZSM-5 molecular sieve catalyst according to claim 4, characterized in that, The metal salt solution of the active component is one or more of the following: soluble zinc salt, iron salt, nickel salt, cobalt salt, molybdenum salt, and zirconium salt. Preferably, the metal salt solution of the active component is Zn(CH3COO)2·2H2O, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O solution, Co(NO3)2·6H2O solution, or (NH4)6Mo7O solution. 24 One or more of the following: ·4H2O solution and Zr(NO3)4·5H2O solution.

7. The method for preparing the modified ZSM-5 molecular sieve catalyst according to claim 4, characterized in that, The ultrasound session lasts for 10-30 minutes, and the settling time is 10-15 hours. The drying temperature is 100-110℃, and the drying time is 10-15 hours; The calcination atmosphere is air, the calcination temperature is 500-600℃, and the calcination time is 5-8 hours.

8. The application of the modified ZSM-5 molecular sieve catalyst according to any one of claims 1-3 in the catalytic pyrolysis of polyolefin plastics to produce aromatic oil.

9. A method for producing aromatic-rich oil by pyrolysis of polyolefin plastics, characterized in that, The polyolefin plastic is mixed with the modified ZSM-5 molecular sieve catalyst according to any one of claims 1-3, and added to a two-stage fixed-bed reactor for pyrolysis under an inert atmosphere.

10. The method for producing aromatic-rich oil by pyrolysis of polyolefin plastics according to claim 9, characterized in that, The mass ratio of the modified ZSM-5 molecular sieve catalyst to the polyolefin plastic is (1-4):1; The pyrolysis temperature is 450-700℃, and the pyrolysis time is 30-60 min.

Citation Information

Cited By

  • Preparation method of catalyst for waste plastic cracking

    CN121892199A

  • Regeneration method of carbon deposition molecular sieve catalyst

    CN122006801A